Answer:
Explanation:
Here the function is f(x) = 7 - 8x. x is the independent variable. f(a) is the value of the function when x = a.
To find the value of f(a), we start with f(x) = 7 - 8x and replace each instance of x with a:
f(a) = 7 - 8a
To find the value of f(a + h), we start again with f(x) = 7 - 8x, but this time we replace each instant of x with (a + h):
f(a + h) = 7 - 8(a + h), or 7 - 8a - 8h.
To find f(a + h) - f(a), we write out the terms of f(a + h) followed by those for f(a) and then combine like terms:
7 - 8a - 8h - {7 - 8a) => -8h
Thus,
f(a + h) - f(a) = -8h